Показники ефективності та необхідність контролю зовнішньоекономічної діяльності підприємств - Журавльова, Є.П. (Культура народов Причерноморья, 2013)
У стати розглянуті основні групи показників: загальна характеристика зовнішньоторговельної діяльності підприємств регіону; показники ефективності зовнішньоторговельної діяльності підприємств ре-регіону; показники експортної орієнтації підприємств регіону; показники оцінки іноземних інвестицій. Розглянуто основні прийоми, що дозволяють зберегти діяльність підприємства і підтримувати ефективну торгівлю на зовнішньому ринку, а також пріоритетні напрямки аудиту зовнішньоекономічної діяльності. В статье проанализированы основные группы показателей: общая характеристика внешнеторговой деятельности предприятий региона; показатели эффективности внешнеторговой деятельности предприятий региона; показатели экспортной ориентации предприятий региона; показатели оценки иностранных инвестиций. Рассмотрены основные приемы, позволяющие сохранить деятельность предприятия и поддерживать эффективную торговлю на внешнем рынке, а также приоритетные направления аудита внешнеэкономической деятельности. Сделан вывод о том, что осуществлять оценку внешнеэкономической деятельности целесообразно по алгоритму, представленному в статье The paper analyzes the main groups of indicators: general characteristics of foreign trade enterprises in the region; performance indicators of foreign trade enterprises region; indicators of export orientation of companies in the region, for the assessment of foreign investment. In addition to the quantitative analysis of economic activity vneshneeko scribed also characterize its qualitative aspects. The basic techniques to keep the activities of the company and maintain effective trading in the foreign market. The above-mentioned techniques, in particular, the author includes: change of specialization importing firm, increased selling prices in the national currency, the registration of existing contracts in the authorized state bodies within the deadlines provided by them in order to execute them on the previous legislation. Besides, there are priorities for the audit of foreign economic activity, which is to focus mainly on monitoring compliance with the terms of export, import and financial contracts that are entered into with foreign partners. It is concluded that assess vneshneekonomiche tion of appropriate on the following algorithm: general charac stick foreign trade enterprises in the region, the evaluation of its effectiveness, the analysis of indicators of export oriented ¬ ING, the inflow of foreign investments, the identification of the most competitive and attractive investment activities the region's economy.